Determinants of Financial Performance with Company Size as A Moderation Variable - Sugeng Kurtikto Wahyudi (Journal of Social Science, 2023)
This is a study of factors that influence profitability and financial performance with moderation of company size to the relationship between profitability and financial performance in government companies in the field of survey business in Indonesia. The study concentrates on the financial management of state-owned enterprises within their operations. The purpose of this study is to determine and analyze the effect of liquidity, leverage and efficiency on profitability and financial performance, as well as the role of moderation of company size on the relationship between profitability and financial performance. Data acquisition through primary data on all branches of the company in the last 11 years so that 143 panel data were obtained as material for further analysis. The analysis model was conducted with the support of SEM PLS and found that liquidity has a negative and significant effect on profitability and financial performance. Leverage and efficiency have a significant effect on profitability. Liquidity, leverage and efficiency negatively and significantly affect financial performance. Profitability and company size have a positive and significant effect on financial performance. The size of the company moderates the relationship between profitability and financial performance.